REVIEW ON ENHANCEMENT OF GLUCOSE UPTAKE AND UP-REGULATION OF GLUCOSE TRANSPORTERS BY ANTIDIABETIC MEDICINAL PLANTS - Ga, Gayathri; MAHALINGAM, GAYATHRI (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Glucose is a key fuel in mammalian cells that import by a process of facilitative diffusion mediated by glucose transporters (GLUT). A defect in GLUT expression for prolong time leads to diabetes mellitus. Medicinal plants used in traditional treatments confirm a possibility of tackling diabetes by regulating the GLUT activity in the body, with lesser side effects. Resistant of tissues to insulin is a major manifestation in type 2, and the cause can be localized in defect of glucose that can be reverse by medicinal plants. In vitro, in vivo, and in silico studies of plant extracts and its active compounds support for their multiple target mechanisms. Many medicinal plants used in the traditional medicine enhancing the translocation of GLUT and this could lead to a new approach for treating type 2 diabetes. Keywords: Diabetes, Glucose transporters, Mechanism of glucose transporter, Glucose transporters 4, Medicinal plants. Â